Critical analysis of the mechanical properties of Dinizia excelsa wood in relation to moisture variations: implications for ABNT NBR 7190:2022 - Fraga, Iuri Fazolin; Arroyo, Felipe Nascimento; Mascarenhas, Fernando Junior Resende; Ruthes, Heloiza Candeia; Soares, Larissa Soriani Zanini RIbeiro; Aquino, Vinicius Borges de Moura [UNESP]; Christoforo, Andre Luis; Lahr, Francisco Antonio Rocco (Brazilian Journals, 2024)
Brazil possesses an extensive forested territory conducive to the prevalence of numerous tree species, including Dinizia excelsa, commonly known as Angelim-Vermelho. The utilization of a wood species in a structural system necessitates a comprehensive analysis of its physical-mechanical properties. In this context, a crucial variable for study is the moisture content, the variations of which, a priori, can significantly impact wood properties. Although the Brazilian code prescribes specific models to adjust strength and stiffness concerning the reference mois-ture, allowing a linear increase as moisture content decreases, this phenomenon may not universally apply to all wood species. Some species may exhibit statisti-cally constant or even decreased values, contradicting code predictions. There-fore, by employing analysis of variance (ANOVA) at a 5% significance level, this research aims to examine the impact of moisture content variation (ranging from 12% to the fiber saturation point – FSP) on 12 mechanical properties of Dinizia excelsa wood. Each type of test involved the creation of 12 specimens, totaling 360 determinations. Among the 12 mechanical properties examined, four showed no significant variations between 12% moisture and the FSP. This suggests that the code formulation inadequately addresses all properties for all wood species. Furthermore, the study revealed that correction models can result in strength val-ues higher than experimentally obtained, thus overestimating structural capaci-ties, and compromising safety. Therefore, a critical reassessment of the existing Brazilian code is imperative.
Análise crítica das propriedades mecânicas da madeira de Dinizia excelsa em relação às variações de umidade: implicações para a ABNT NBR 7190:2022